Business Continuity Management in Manufacturing Enterprises Operating in Poland - Kita, Mateusz; Kłosowska, Bożena (Studia Oeconomica Posnaniensia, 2026)
The article focuses on the significance of business continuity for manufacturing enterprises and the role of insurance in its facilitation . A study of 16 enterprises operating in Poland showing their perception of risk and ways to safeguard against exceptional occurrences is the basis for the analysis. The article highlights potential problems in building resilent organizations in a young free-market economy and suggests actions that can improve the situation.